Undergraduates' charitable work brought them closer to Kuala Pahang community - UMP, PNC

(untitled)
Almost 1,000 people including Universiti Malaysia Pahang (UMP) undergraduates gathered at Kuala Pahang Square to take part in a charity work under Gerak Bakti Siswa 1Malaysia (GBS1M) organised by the university with the cooperation from Majlis Aspirasi Pemangkin Nasional (Aspiration Impetus National Council- MAPAN).